Hubungan Usia, Paritas, Dan Kadar Hemoglobin Ibu Dengan Kejadian Bayi Berat Lahir Rendah (BBLR) Di RSUD Dr. H. Abdul Moeloek Provinsi - Gabrile Madumey, Diora; Nareswari, Shinta (Medula, 2025)
Low Birth Weight (LBW) is defined as a birth weight of less than 2,500 grams. Infants born with low birth weight represent a significant and ongoing health issue, both locally and globally. The occurrence of LBW is multifactorial, and among the various risk factors, most are related to maternal conditions. Based on existing research, several maternal factors that may influence the incidence of LBW include maternal age, parity, and hemoglobin levels. This study employed an observational analytic method with a cross-sectional approach. The research sample consisted of postpartum mothers who delivered LBW infants and met the inclusion and exclusion criteria at Dr. H. Abdul Moeloek Regional General Hospital (RSAM) from January 2020 to November 2021, totaling 135 subjects. The independent variables in this study were maternal age, parity, and hemoglobin levels, while the dependent variable was the incidence of LBW, classified into small-for-gestational-age (SGA) and appropriate-for-gestational-age (AGA). The sampling technique used was total sampling. The results showed that maternal age was significantly associated with the incidence of LBW, with a p-value of 0.037 (<0.05), and maternal hemoglobin level was also significantly associated with LBW, with a p-value of 0.024 (<0.05). However, parity was not associated with the incidence of LBW, as indicated by a p-value of 0.111 (>0.05). In conclusion, maternal age and hemoglobin levels are associated with the incidence of LBW, whereas parity is not.